The Physical Performance Needs in Silat Olahraga - Mohamad Nizam Mohamed Shapie; Dahlia Al-Syurgawi; Hazim Samsudin; Syahida Mohd Nazri; Nasru Syazwan Nawai (Universitas Negeri Padang, 2022)
Study Purpose. Combat sports have been classified as grappling, for example, karate, silat, taekwondo, jitsu, judo, wrestling) and striking, as silat, karate or taekwondo depending on their rules and technical actions. As the technical movement and rules vary depending on the sport, it is plausible that physical fitness necessities to achieve high-level in each combat sport are also different. Materials and Methods. Despite their determination and identity, the physical and physiological profiles of all combat sports, there were less investigation can be proven on the effects of plyometric training in silat. Results and Discussions. This current information could be useful for athletes’ detection programs for the different combat sports. Based on the past research that have been done, it’s have been proved that less research is being done on plyometric training in silat and predominantly on the main physical fitness performance needs (power, agility, cardiovascular endurance, and muscular strength). Conclussions. Coach as a full drill power in kick and hand